2011
DOI: 10.1142/s0217751x11053663
|View full text |Cite
|
Sign up to set email alerts
|

A NEAR HORIZON CFT DUAL FOR KERR–NEWMAN AdS

Abstract: We show that the near horizon regime of a Kerr–Newman AdS (KNAdS) black hole, given by its two-dimensional analogue a là Robinson and Wilczek (Phys. Rev. Lett.95, 011303 (2005)), is asymptotically AdS2 and dual to a one-dimensional quantum conformal field theory (CFT). The s-wave contribution of the resulting CFT's energy–momentum tensor together with the asymptotic symmetries, generate a centrally extended Virasoro algebra, whose central charge reproduces the Bekenstein–Hawking entropy via Cardy's formula. Ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 59 publications
3
33
0
Order By: Relevance
“…In addition, although we have investigated the photon orbits in quite general spacetimes for the static case, we have only investigated asymptotically flat Kerr and Kerr-Newman black holes in the non-static case. It would therefore be interesting to see if in the asymptotically AdS case, the photon orbits of Kerr-Newman black holes behave in a similar way (it is already known that a stable photon orbit exists inside the inner horizon of an asymptotically anti-de Sitter Kerr-Newman black hole [82]) and what -if any -implication this has on holography [83]. …”
Section: Conclusion: Light On the Event Horizon Of Extremal Black Holesmentioning
confidence: 99%
“…In addition, although we have investigated the photon orbits in quite general spacetimes for the static case, we have only investigated asymptotically flat Kerr and Kerr-Newman black holes in the non-static case. It would therefore be interesting to see if in the asymptotically AdS case, the photon orbits of Kerr-Newman black holes behave in a similar way (it is already known that a stable photon orbit exists inside the inner horizon of an asymptotically anti-de Sitter Kerr-Newman black hole [82]) and what -if any -implication this has on holography [83]. …”
Section: Conclusion: Light On the Event Horizon Of Extremal Black Holesmentioning
confidence: 99%
“…In that case, the expressions for the diffeomorphism invariance given by Eqs. (21), (22), (23), and (24) become…”
Section: Cft In Nonextremal Rotating Black Holementioning
confidence: 99%
“…Since the successful description of the holographic duality between the geometry near the horizon of extremal Kerr black hole and the conformal field theory [1][2][3][4][5], there have been many studies for the holographic duality in various black holes [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The holographic duality has been also developed for near extremal black holes by introducing the extremal parameter [15,17] or calculating the graybody factor [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the resulting two dimensional theory is much simplified by considering the region U ∼ , since mixing3 This statement extends to all the Gauss-Bonnet invariants 4. In[43] it was shown that ϕ lm decays exponentially fast in time by analyzing the asymptotic behavior of its field equation for higher orders in l and m.…”
mentioning
confidence: 94%
“…Our computational construction mirrors that of [43,44], where the near horizon isotropy is exploited to dimensionally reduce physics to two dimensions a la Robinson and Wilczek [45]. The idea is that most four dimensional near horizon geometries exhibit a sort of splitting:…”
Section: Introductionmentioning
confidence: 99%